Nas ondas do surfe: estilos de vida, territorialização e experimentação juvenil no espaço urbano - Albuquerque, Cynthia Studart (2006)
This work is the result of the ethnographic study I conducted on the relationships built between the young surfers and urban spaces. Ways to use, appropriation and experimentation that makes surfing a lifestyle, a unique way of being, living and occupying the city. The study sought to describe, interpret and analyze the ways in which young people take ownership of the style-surfing and a new meaning in their relationship with oneself, others and with the public space of the beach. Since the research was an anthropological one, I decided to focus on the techniques of participant observation, field diary, interviews, and above all, peaceful coexistence, dialogue, moments-free enjoyment of youth styles. At the beginning of the text, I present the subject matter, my journeys in the research, choices and experiences, well beyond the characteristics that define the style of living-surfing: lightness, quickness, exactitude, visibility and multiplicity. It follows with a discussion about the elements that make up the style-surfing: the ethos-surfing, surfing the look-and the rituals of sociability. A methodological strategy was the perception of the diversity present in the surf world, having a multitude of ways to be surf-existent, so I opted to build a typology of practices present in the coastal area surfing: surf-fashion-pleasure surfing, surf- Leisure and surf art. The ethnography as a methodological option was also performed in order to further study in specific subjects such as universal symbols of Icaraí peaks and the East-West, to understand the logic, the disputes, the hierarchies and distinctions produced in each occupation, mode of expression and visibility of young people in urban space. The research showed that surfing as a lifestyle with its limits and different uses is for these young people the opportunity to exercise their preferences, experimentation, entertainment, amusement, occupation, business, finally able to live a life worthy of his youth.